O campo tem cor?: presença/ausência do negro no currículo da educação do campo no Pará - MAGALHÃES, Leila de Lima (Universidade Federal do Pará, 2012)
The main focus of this paper is to investigate about the presence/absence of the Negro in the syllabus of Education in the Countryside on the scope of the Forum Paraense of Education in the Countryside, an expression of Paraense Movement for an Education in the Countryside. As a starting point, the writer performed an exploratory study over the actions taken by the Forum and, through documents and interviews, aimed at identifying to what extent the ethnic-racial relations, from Act 10639/03 on, are included in the educational and curricular proposal of the Forum. Together with that, she sought to make a dialog with the literature which deals with Education in the Countryside as a specific field, and with the Ethnic-racial Relations. For that, she used the qualitative methodology reference as a means of analysis and propose strategies to dynamize the ethnic-racial relations in the education in the countryside on the State of Para.